Comprehensive analysis of tissue proteomics in patients with papillary thyroid microcarcinoma uncovers the underlying mechanism of lymph node metastasis and its significant sex disparities - Cao, Zhen; Zhang, Zejian; Tang, Xiaoyue; Liu, Rui; Wu, Mengwei; Wu, Jianqiang; Liu, Ziwen (Frontiers in Oncology, 2022)
Background: Lymph node metastasis (LNM) in papillary thyroid microcarcinoma (PTMC) is associated with an increased risk of recurrence and poor prognosis. Sex has been regarded as a critical risk factor for LNM. The present study aimed to investigate the molecular mechanisms underlying LNM and its significant sex disparities in PTMC development. Methods: A direct data-independent acquisition (DIA) proteomics approach was used to identify differentially expressed proteins (DEPs) in PTMC tumorous tissues with or without LNM and from patients of different genders with LNM. The functional annotation of DEPs was analysed using bioinformatics methods. Furthermore, The Cancer Genome Atlas Thyroid Carcinoma (TCGA-THCA) dataset and immunohistochemistry (IHC) were used to validate the selected DEPs. Results: The proteomics profile in PTMC with LNM differed from that of PTMC without LNM. The metastasis-related DEPs were primarily enriched in the categories associated with mitochondrial dysfunction and may promote tumor progression by activating the oxidative phosphorylation and PI3K/AKT signaling pathways. Comparative analyses of these DEPs revealed downregulated expression of specific proteins with well-established links to tumor metastasis, such as SLC25A15, DIRAS2, PLA2R1, and MTARC1. Additionally, the proteomics profiles among PTMC patients of different genders with LNM were dramatically distinguished. An elevated level of ECM-associated proteins might be related to more LNM in male PTMC than in female PTMC. The upregulated expression levels of MMRN2 and NID2 were correlated with sex disparities and showed a positive relationship with unfavorable variables, such as LNMs and poor prognosis. Conclusions: The proteomics profiles of PTMC show significant differences associated with LNM and its sex disparities, which further expands our understanding of the functional networks and signaling pathways related to PTMC with LNM.